The phytoestrogen genistein enhances multidrug resistance in breast cancer cell lines by translational regulation of ABC transporters - Rigalli, Juan Pablo; Theile, Dirk; Weiß, Johanna (Cancer letters, 2016)
Breast cancer is the most frequent malignancy in women. Multidrug resistance due to overexpression of ABC drug transporters is a common cause of chemotherapy failure and disease recurrence. Genistein (GNT) is a phytoestrogen present in soybeans and hormone supplements. We investigated the effect of GNT on the expression and function of ABC transporters in MCF-7 and MDA-MB-231 breast cancer cell lines. Results demonstrated an induction at the protein level of ABCC1 and ABCG2 and of ABCC1 in MCF-7 and MDA-MB-231, respectively. MCF-7 cells showed a concomitant increase in doxorubicin and mitoxantrone efflux and resistance, dependent on ABCG2 activity. ABCC1 induction by GNT in MDA-MB-231 cells modified neither drug efflux nor chemoresistance due to simultaneous acute inhibition of the transporter activity by GNT. All inductions took place at the translational level, as no increment in mRNA was observed and protein increase was prevented by cycloheximide. miR-181a, already demonstrated to inhibit ABCG2 translation, was down-regulated by GNT, explaining translational induction. Effects were independent of classical estrogen receptors. Results suggest potential nutrient-drug interactions that could threaten chemotherapy efficacy, especially in ABCG2-expressing tumors treated with substrates of this transporter.
Gesehen am 21.10.2021